Analisis Kemampuan Pemecahan Masalah Matematisc: Dampak Pembelajaran Flipped Classroom Dan Habits Of Mind Berbantuan Aplikasi Exe-Learning - Fitriani, Rahayu; Supriadi, Nanang; Widyastuti, Rany (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
Modern mathematics education must shift from merely "knowing" mathematics to "doing" mathematics. This "doing" process inherently demands strong problem-solving skills, which can only flourish in students who have internalized Habits of Mind as part of their intellectual character. In this study, we report on the effect of a flipped classroom learning model, assisted by the eXe-Learning application, on the mathematical problem-solving abilities of students with high, moderate, and low categories of Habits of Mind. This study employed a quantitative method with a quasi-experimental design. The sampling technique used was cluster random sampling, with classes serving as the clusters. Research data were collected using two types of instruments: test and questionnaires. The data were analyzed using a two-way ANOVA with unequal cell sizes, preceded by prerequisite tests for normality and homogeneity. Based on the analysis, it can be concluded that the flipped classroom model assisted by the eXe-Learning application has a significant effect on both students' mathematical problem-solving abilities and their Habits of Mind. However, the interaction between the flipped classroom model and students' Habits of Mind did not have a significant effect on their mathematical problem-solving abilities. Keywords: Flipped classroom; problem-solving skills; exe-learning; habits of mind